Interleukin-10 promoter polymorphism and venous thrombosis - Cochery-Nouvellon, Eva; Vitry, Fabien; Cornillet-Lefebvre, Pascale; Hezard, Nathalie; Gillot, Lucile; Nguyen, Philippe (Thrombosis and Haemostasis, 2006)
The human interleukin-10 promoter gene is highly polymorphic. IL-10 polymorphisms have been associated with various autoimmune and lymphoproliferative disorders. Although IL-10 has been shown to modulate thrombin generation in several experimental models, it is not known whether IL-10 polymorphisms could be a risk factor for venous thrombosis. We therefore conducted a case-control study comparing 74 consecutive patients who experienced at least one episode of documented venous thromboembolic event and 100 healthy controls. All subjects were Caucasians. Five polymorphisms of the IL-10 promoter gene were studied: two highly polymorphic dinucleotide repeats, IL-10 R and IL-10G, and three single nucleotide polymorphisms at position −1082, −819 and −592. Factor VG1691C Leiden mutation was systematically determined. Multivariate logistic regression analysis showed that IL-10 G13 and G10 alleles are independent risk factors for venous thrombosis (Odds ratio:OR = 3.33, p = 0.003 and OR = 2.83, p = 0.03, respectively). Furthermore, IL-10 G10 allele is more frequent in recurrent disease.
Keywords: Deep vein thrombosis; interleukin-10; factor V Leiden; hereditary thrombosis risk factor